Resistant Streptococcus pneumoniae strains in children with acute otitis media– high risk of persistent colonization after treatment - Izabela Korona-Glowniak; Piotr Zychowski; Radoslaw Siwiec; Elżbieta Mazur; Grażyna Niedzielska; Anna Malm (BMC Infectious Diseases, 2018)
Abstract Background Despite advances in the development of pneumococcal conjugate vaccines, acute otitis media (AOM) is a common childhood infection, caused mainly by Streptococcus pneumoniae. It has been suggested that persistence of pneumococcal nasopharyngeal carriage is a risk factor for subsequent recurrent infections. Methods In this study we evaluate the relationship between 55 pneumococcal strains obtained from nasopharynx/oropharynx (NP/OP) and middle ear fluid (MEF) of 62 children, aged between 1 and 16 years, during AOM (including recurrent/treatment failure AOM, and post-treatment visits), based on their phenotypic and genotypic characteristics performed by analyses of serotype, antibiotic susceptibility patterns and multilocus sequence typing. Results S.pneumoniae was isolated from 27.4% of MEF samples; it constituted 43.6% of all positive bacterial samples from MEF samples. There was statistically significant concordance between isolation from the MEF sample and NP/OP colonization by S. pneumoniae (p < 0.0001). During post-treatment visits S.pneumoniae was isolated from 20.8% of children; 91% of them were positive in pneumococcal NP/OP culture during AOM. The serotypes belonging to 10- and 13-valent pneumococcal conjugated vaccines constituted 84% and 92% of the strains, respectively. Multidrug resistance was found in 84% of the strains. According to multivariate analysis, pneumococcal colonization after antibiotic therapy was significantly associated with shorter length of therapy in children with bilateral AOM. Conclusions High persistent prevalence of antibiotic-resistant S.pneumoniae strains in children with AOM after unsuccessful bacterial eradication may presumably be regarded as a predisposing factor of infection recurrence.